Single lung transplantation in a patient with retrospective positive cross-match - Lesińska, Anna Justyna; Piotrowska, Maria; Dec, Paweł; Wasilewski, Piotr; Kubisa, Anna; Pieróg, Jarosław; Wójcik, Norbert; Czarnecka, Michalina; Kubisa, Bartosz; Grodzki, Tomasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Lung transplantation is a method useful in such non-malignant end-stage parenchymal and vascular diseases as: chronic obstructive pulmonary disease (COPD), idiopathic interstitial pulmonary fibrosis, cystic fibrosis, or primary pulmonary hypertension. The main aim of this procedure is to extend the patient’s lifespan and quality of life. However, the availability of the operation is limited by organ access. In this paper we present the case of a 58-year-old female in the fourth stage of COPD, who was classified to have a single lung transplantation. Because of some technical problems it was decided to transplant a left donor lung in the right recipient lung locus. Positive cross match was demonstrated retrospectively, and we applied five courses of plasmapheresis. Human immunoglobulin and rituximab treatment were performed to decrease the impact of lymphocytotoxic antibodies. The patient survived 498 days after transplantation, 271 in the hospital.